1983
DOI: 10.1055/s-2007-1018659
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor of Erythrocytes and Glucose Metabolism in Uremic Children

Abstract: This study represents the results of oral glucose tolerance test (O-GTT) of 28 children with chronic renal failure, including 12 undialyzed and 16 dialyzed cases, compared to their own insulin receptors of erythrocytes. 7 of the 12 undialyzed patients (58.3%) represented abnormal O-GTT, while in dialyzed patients 3 of 16 cases (18.8%) had abnormal O-GTT. The maximum binding of 125 l-insulin to erythrocytes, 6.34 ± 1.93% in dialyzed patients, was significantly lower (p < 0.05) than 7.73 ± 1.03% in controls, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Most findings were based on oral glucose tolerance tests [7, 14]. There is controversy about intravenous glucose tolerance tests [15], and there is a striking difference between up to 50% pathological oral glucose tolerance tests in children with renal insufficiency and the fact that (apart from children with infantile cystinosis) hardly any of these children develop overt diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most findings were based on oral glucose tolerance tests [7, 14]. There is controversy about intravenous glucose tolerance tests [15], and there is a striking difference between up to 50% pathological oral glucose tolerance tests in children with renal insufficiency and the fact that (apart from children with infantile cystinosis) hardly any of these children develop overt diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible side effects of GH, a disturbed glucose tolerance and induced hyperinsulinemia have raised concerns [4, 5] since the long-term effects of rh GH-induced hyperinsulinemia are unknown. The data on glucose tolerance in patients with UTS and CRF are limited to glucose and insulin measurements using oral glucose tolerance tests [6, 7]. In order to investigate both the early and second (or metabolic) insulin secretion phases, we routinely used an intravenous glucose infusion test (GIT) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The patients were not taking any medication known to affect carbohydrate metabolism. The primary renal disease responsible for the renal failure was chronic glomerulonephritis [44], polycystic kidney disease [7], chronic inter stitial nephropathy [10], arteriolar nephrosclerosis [3] and familiar nephropathy [2]. Ages (years ± SEM) were 36.9 ±1.4 for controls, 38.7 ±3.7 for U, 33.1 ±2.9 for HD, and 39.2±3.4 for CAPD.…”
Section: Subjectsmentioning
confidence: 99%
“…Studies from several laboratories have yielded conflicting results regarding insulin binding to cells from uremic individu als. Several studies have reported normal insulin binding to cells from uremic patients [3][4][5][6] or from uremic rats [7,8], Others, however, have reported decreased insulin binding to cells from uremic [9][10][11] or dialysis patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…The method used for the measurement of insulin binding to erythrocytes has now been improved (Namikawa et al, 1983) and can easily be used in children because only small amounts of blood are required to perform the test. It is also known that the insulin receptor in erythrocytes usually runs parallel to the insulin receptor in the monocytes or the adipocytes (Dons et al, 1981;Caro andAmatruda, 1982, Ward et al, 1981), and in view of these facts, we used erythrocytes to investigate the insulin receptor analysis in the present study.…”
mentioning
confidence: 99%